Development of Sharia Business Models for Technology Startups - Arifin, Agus Zainul; Nainggolan, Christine Dewi; Tanuwijaya, Haryanto; Cale, Wolnough (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Indonesia has seen rapid growth of technology startups in recent years. However, many startups have yet to capitalize on the sharia business model, which can be an attractive alternative to address social and economic challenges. The main objective of this study is to develop a sharia business model that is suitable for technology startups in Indonesia. Specifically, this study aims to identify the key elements of a sharia business model that are relevant for technology startups, analyze the benefits and barriers of implementing a sharia business model in the technology industry, and formulate an effective implementation strategy for technology startups to adopt a sharia business model. This study uses a combination of qualitative and quantitative methods. In the first stage, the literature was thoroughly studied and interviews were conducted with sharia business experts and technology startup activists to determine the main components of the sharia business model. The results of the study indicate that the main components of the relevant sharia business model for technology startups include the principle of profit sharing (profit sharing), prohibition of riba (interest-free financing), and fairness and transparency in transactions. The survey results also show that most technology startup founders see the sharia business model as an alternative that can attract investors and consumers. This study found that technology startups in Indonesia have great potential to implement a sharia business model if there is a strong effort to educate and provide resources.